Remarks at China’s 1+6 Roundtable with Premier Li Keqiang - Malpass, David (World Bank, Washington, DC, 2020)
World Bank Group President David Malpass spoke about the broad, rapid, and affordable access to Coronavirus (COVID-19) vaccines which will be at the core of a resilient economic recovery that lifts everyone. He mentioned that the World Bank Group’s forty-year engagement with China has been mutually beneficial and continues to evolve. He thanked China for its large contribution to IDA19, which is particularly noteworthy given China’s stage of development. He highlighted on the lending relationship with China which is also evolving steadily, with a strong focus on analytical and advisory services and strong engagement from the International Finance Corporation. He expressed that China’s economy needs further reform to get the most benefit as it returns to sustained growth. China’s Coronavirus (COVID-19) economic policy response has been weighted towards supporting firms and banks and encouraging public investment, in relative terms, while direct transfers to households have been limited. Greening of China’s growth going forward should form a core objective of the fourteenth five-year plan. Regarding progress on debt relief and transparency, he mentioned that private creditors have not been participating, leaving official bilateral creditors shouldering much of the burden.